Fiscal Decentralization in Sikka Regency: Analyzing Local Financial and Intergovernmental Transfers - Lusiana Florentin Werang, Maria (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Fiscal decentralization in Indonesia is interpreted as an essential governance effort to empower local governments and encourage regional economic development. In this regard, this study focuses on the fiscal analysis of Sikka Regency in the 2020-2024 period, with aspects of independence, dependence, and effectiveness through a descriptive quantitative approach to understand and analyze how the existing level of financial management supports financial governance through a fiscal decentralization framework. Then, the research findings reveal challenges in the concretization of budgetary decentralization, which shows an average fiscal independence ratio of only 0.7%, high dependence of 96.3%, and budgetary effectiveness obtained by 80.44%. Thus, this practice highlights the ongoing limitations in formulating local revenues. Finally, I provide recommendations that in the practice of fiscal decentralization, policymakers must be committed to designing a more focused and context-sensitive strategy from the practice of budgetary decentralization in supporting regional development through credible and adaptive financial governance.